Design and development of temperature collection system on solid granular beds - Xin Lu, Jincao Chen, Dianjin Liu, Yaozhong Chen, Ke Jiang (Journal of Information & Systems Management, 2017)
On the basis of analyzing the heat transfer performance of solid granular beds, an unsteady-state heat conduction model describing the temperature change of the grains is built and the finite-difference implicit schemes are theoretically deduced using the volume equilibrium method for numerical simulation. The validation of the numerical model is checked through compared with the experimental results. A temperature collection system is designed and developed. As a part of the system, an initial temperature simulator for measuring the initial temperature of grains is also developed according to the similarity principle. This system can accurately measure the temperature field and real-time average temperature of the grains and simultaneously transfer the temperature information to the computer terminals through the controller area network bus.